Synthesis and Characterization of Zeolitic Imidazolate Framework-8 (ZIF-8)/Al2O3 Composite - Aulia, Wulan; Ahnaf, Ahnaf; Irianto, Mochammad Yusuf; Ediati, Ratna; Iqbal, Rendy Muhamad; Rachman, Rahadian Abdul; Martia, Ulva Tri Ita (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
Metal-organic framework (MOF) such as ZIF-8 is the tremendous porous material applied in many fields due to high specific surface area and excellent regularity of pores. One technique to improve the physical properties of ZIF-8 with the formation of a composite between a metal oxide and MOF. ZIF-8 and ZIF-8/Al2O3 were successfully synthesized by the solvothermal method with an Al variation of 19%, 38%, and 76%. The ZIF-8/Al2O3 were characterized by XRD, FTIR, SEM, and N2 Physisorption. The diffractogram shows that the appearing of ZIF-8’s peak on 2θ = 7.26; 10.41, 12.66, 16.41, and 17.95°. The morphological of ZIF-8 crystals had a cubic shape. Then the ZIF-8/Al2O3 had different shapes with ZIF-8. Based on the FTIR result, the Zn-N peak appears on 420 cm−1, which indicates the bonding between metal and organic ligand for ZIF-8/Al2O3 has an additional spike on 825 cm−1 due to the vibration of Al−O− Al.